The Marriage of Siri between Private Piety and Public Legal Order: The Dialectic of Islamic Law and the New Indonesian Criminal Code - Ahmad Nurozi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Siri marriage is considered valid under Islamic law but lacks state recognition because it is not officially registered. Although often viewed as an expression of private religious observance, this practice may create significant legal consequences, particularly for the protection of women’s and children’s rights. This article examines siri marriage through the dialectical relationship between Islamic law and Indonesian positive law, with reference to recent criminal law reforms. Using a normative juridical approach supported by conceptual and socio-legal analysis, the study applies maqāṣid al-sharī‘ah and ta‘zīr to assess the legitimacy of state intervention. The findings indicate that siri marriage cannot be understood solely as religious freedom because it may generate legal vulnerability and structural injustice. Consequently, compulsory marriage registration and victim-oriented legal measures may be justified constitutionally and within Islamic legal principles. Regulating siri marriage should therefore be understood not as the criminalisation of religion, but as an effort to harmonise private piety with justice, public welfare, legal protection, and certainty.